Faktor – faktor yang melatarbelakangi terjadinya Fraud: Studi Empiris pada KAP di Jakarta Timur - Ahmad Subaki; Akhmad H Abubakar; Faizal Ridwan Zamzany; Fikri Hidayat (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research was conducted to uncover factors that are likely to have an impact on audit fraud. The research was conducted using descriptive quantitative research methods. This descriptive quantitative research uses a closed questionnaire method in data collection. The sample data obtained in this research was 148 respondents. The data obtained is then processed using SPSS statistical software version 22. From this research, it was found that audit fees, audit tenure, independence, work experience have a negative and significant impact on audit fraud